The Destruction of Hyderabad - Mr. Muhammad Hassan Sohail (CISS Insight Journal, 2016)
The Destruction of Hyderabad is a comprehensive account of the last days of Hyderabad as a princely state. The book covers behind the scene moves of protagonists leading to the final act of Indian army action on 14th September 1948 and absorption of the state in Indian Union. With this final act was unique Hyderabadi culture also met a sad end to its development in which Hindus and Muslims had contributed equally. The final act of destruction of Hyderabad was precipated by attacks of Razakars on the Hindu community which according to the author had the tacit approval of the Nizam. Razakar attacks further vitiated an already charged political situation and provided the Indian government with a pretext to move in its army and annex Hyderabad. It also caused the massacre of Muslims who were disarmed, at the hands of Hindus who were allowed to retain their weapons by the Indian Army. It may lso be of interest to note that planning for moving in Indian troops in Hyderabad had begun as early as January 1948 and it was in reaction to acts of Razakars. A.G.Noorani is a well-known Indian lawyer, historian, newspaper columnist and a dedicated researcher. He is the author of over 10 books which include Kashmir Dispute(1947-2012), Islam and Jihad and India – China Boundary Problems.